Dosis y frecuencia de aplicación de fósforo y potasio en cinco gramineas tropicales. - Monsalve, Sigifredo A.; Martinez W., Orlando (Instituto Colombiano Agropecuario, 2019)
An study was conducted under field conditions at the Truipaná Experimental Station, located in Cereté, Córdoba, at 13 meters of elevation with a -nean temperature of 28°C and an average annual precipitation of 1,112 mm, with the following objetives: To determine the tii."t of different levels of P and K on the forage production of angletongrass (Dichanthium aristatum (Poir) Hubbard), napiergrass (Pennisetum purpureum Schumach), guineagrass (Panicum maximum Jacq.), pangolagrass (Digitaria decumbens Stent), and paragrass (Brachiaria mutica (Forsk) Stapf). To study me frecuency of application of these elements to obtain a constant and high yield of forage. The soil was a clay loam with pH 6,7. Three levels of P2 05and K2 0: 0, 50 and 100 kg/Ha were applied initially. Nitrogen, 50 kg/Ha was uniformly applied after each harvest. The results obtained in this study indicated that P and K applications did not have a significative effect on forage production of all the grasses studied except for napiergrass. Phosphorus (P2 05 ) levels of 50 and 100 kg/Ha had significative effects on the increment of forage production by napiergrass. The application of high levels of both P and K had depressive effects on forage production of angletongrass and guineagrass, and the K on napiergrass. A positive and highly significative interaction was found between P and K for angletongrass and guineagrass. For napiergrass the interaction between P and K was significant and positive for the levels of 100 kg/Ha of P2 05and 50 kg/Ha of K2 0. In contrast, the interaction between K and P was significative and negative for the levels of 100 kg/Ha of K2 0 and 50 kg/Ha of P2 05 . The grasses studied have different requirements of P and K, being the requirements of these elements for napiergrass higher than for the other species included in this study. The forage yield of angletongrass, guineagrass, pangolagrass and paragrass is not increased due to the addition of P and K for a period of three years after planting the grasses. Napiergrass yield, in contrast, can be increased applying 50 kg/Ha of P2 05 two years after the establishment of the pastures on the soils of the Turipaná Experimental Station.